EXPERIMENTAL STUDIES OF THE CAUSES OF OVERLOADS IN HYDRAULIC SYSTEMS OF STANDARD PRESSES FOR CUTTING LIGHT INDUSTRY PARTS HAVE BEEN PERFORMED - ZALYUBOVSKYI, MARK; PANASYUK, IGOR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Studies of the operation of hydraulic cutting presses such as "PVG 8-2-0" and "PVG 8". These types of hydraulic presses are used in light industry in the manufacture of footwear. In particular, the presses of the "PVG 8-2-0" and "PVG 8" types are used for cutting rubber and cardboard parts of the shoe bottom. Experimental studies of the causes of overloads in hydraulic systems of these types of presses have been carried out. It is established that at the end of the process of cutting each part there is a sharp significant abrupt increase in pressure in the hydraulic system. This increase in pressure occurs due to the formation of a rigid system drummer - cutter - plate. Such constant cyclic pressure fluctuations negatively affect the operational characteristics of the equipment, in particular, lead to premature wear of the working tool and breakage of parts of hydraulic systems. Analytical studies were also conducted. On the basis of analytical researches the calculation of size of "jumps" of pressure in hydraulic systems of presses is executed, and also the factors influencing size of overloads are revealed. It is established that one of the main factors influencing the amount of overload is the rigidity of the system. Mathematical dependences between the modulus of elasticity of metal elements of the hydraulic system, their geometrical parameters and the value of pressure drop are obtained. Exhaustive recommendations are given to improve the design of presses, which create conditions for reducing overloads in their hydraulic systems during the process of cutting parts. It is established that to reduce overloads during felling in hydraulic systems of presses it is necessary to add elastic elements - tanks with an air cushion or the spring-loaded piston (accumulators), short sections of pipelines with elastic walls which will provide possibility of their temporary elastic diametrical deformation. A method for calculating the amount of pressure injection in the hydraulic systems of standard presses on the example of the press "PVG 8-2-0" is proposed. The obtained research results can be useful and used in the relevant design offices of machine-building enterprises at the design stage of this equipment.
Keywords: cutting press; cutter; shoe parts; hydraulic system; pressure charges